(In)sustentabilidade turística no estuário do Rio Vaza-Barris/SE : perspectiva analítica da legislação vigente - Conceição, Sabriny Sueley Oliveira da (2015)
Tourism in natural areas have become targeted by tourist's interests. Such preference is justified by landscape and aesthetic's value, as well as the need for recreation and leisure activities of individuals. The tourism industry, aiming profitability, appropriates themselves of such reality by means of a discourse based on sustainability. Such scenario has already reached the State of Sergipe, which has a diversity of splendiferous landscapes and a cultural diversity that express tourist potentialities. Vaza-Barris estuary is engaged in this context, since it has been touristic explored, specifically, after the construction of Orla Pôr do Sol (Sunset Edge) and Joel Silveira's brigde. In this sense, the activities that occur in the estuary, specifically, on Pôr-do- Sol Orla, Ilha da Paz (Island of Peace), and Ilha Paraiso (Paradise Island), are being damaged by touristic activities and these places don't have any kind of management plan, which has been compromising the local sustainability. In this context, this study aimed to analyze the sustainability of tourist's activities developed at the estuary of Vaza-Barris’s River, since these Islands are areas of intense touristic visitation as well as they are considered Permanent Preservation Areas (APP's) but they don't present until now any kind of management plans. As methodology we used exploratory research, documentary and bibliographic, and data collection instruments such as: questionnaires, observation of the study area and semi-structured interviews with the residents of the locality and Public bodies. Reach the conclusion that the systematic examination of the relationship between the General Law of Tourism, public policies for sustainable tourism in Sergipe State and the reality of tourism in the Mosqueiro Village hasn't showed favorable trends for sustainability, being necessary a intervention from the public bodies of tourism and the public bodies of environmental government in order to elaborate a plan for public use of this places as well as it is required the participation of the local community to partake the benefits from the tourism of the area.